The Effect of Interest in becoming a Sharia Bank Customer to Students of FEBI Universitas Suryakancana, Indonesia - Sobana, Dadang Husen; Anjani, Melani Salsabila (Department of Sharia Financial Management, Institut Agama Islam Negeri Sultan Amai Gorontalo, Indonesia, 2021)
This research is motivated by the main problem which considers the concept of Islamic banks to be the hsame as conventional banks. This study aims to describe the effect of prevention and knowledge of Islamic banking products on the interest in becoming a customer of Islamic banks in FEBI students of the Surya Kencana University. The method used is descriptive with a quantitative approach. The population was 581 FEBI students, so that the sample was taken by random sampling using the Slovin formula and obtained 86 respondents. The data analysis technique used multiple linear regression, coefficient of determination test, and hypothesis testing. The results of the study concluded that partially the motivation to avoid usury had an effect on the interest in becoming a sharia bank customer in FEBI students. No doubt with a contribution of 21.9%. Then, knowledge of Islamic banking products affects the interest in becoming a customer of Islamic banks in FEBI Elements students with a contribution of 46.4%. Simultaneously, avoiding usury and product knowledge have an effect on interest in becoming a sharia bank customer in FEBI Element students with a contribution of 68.3% with a strong coefficient proportion. While the remaining 31.7% is influenced by other factors outside the variables not examined with a low proportion coefficient.